Weed infestation of crops of winter spelt wheat (Triticum aestivum ssp. spelta) cultivars grown under different conditions of mineral fertilization and chemical plant protection - Sylwia Andruszczak (Acta Agrobotanica, 2012)
A field experiment was carried out in the years 2008-2010 on rendzina soil. The aim of the study was to evaluate weed infestation of winter spelt cultivars (‘Schwabenkorn’ and ‘Spelt I.N.Z.’) grown under different conditions of mineral fertilization and chemical plant protection. In the experiment, two levels of mineral fertilization were compared (kg × ha-1): I. N 60; P 26.2; K 83; and II. N 80; P 34.9; K 99.6. The che- mical protection levels were as follows: A. Control treatment; B. Mustang 306 SE, Stabilan 750 SL; C. Mustang 306 SE, At- tribut 70 WG, Stabilan 750 SL; D. Mustang 306 SE, Attribut 70 WG, Alert 375 SC, Stabilan 750 SL. Apera spica-venti, Setaria pumila, and Galium aparine occurred in greatest numbers in the spelt wheat crop. The cultivar ‘Schwabenkorn’ was more competitive against weeds. The number of dicotyledonous and monocotyledonous weeds, their total number, and air-dry weight of weeds in the crop of this cultivar were significantly lower compared to cv. ‘Spelt I.N.Z.’. Chemical protection of spelt wheat decreased weed dry weight compared to the control treatment without chemical protection. The application of higher rates of mineral fertilizers slightly increased the number of weeds but did not influence their dry weight and number of weed species.